Body Image and Its Relationship With Self – Confidence In Female College of Physical Education and Sport Sciences Students - Ali, Suha; Ismael, Huwaida (Journal of Physical Education, 2017)
Self image is one of the most important aspects that affect personality, which may have a great impact, whether negative or positive is a mental image of the individual about himself. Self-confidence is an acquired factor and there is something that can be activated to enhance your self-confidence, such as the positive image of the body. The body image has psychological dimensions and has a great impact on personality and behavior. It is a mixture of cognitive, emotional and behavioral components. The research aimed at identifying the relationship between body image and self-confidence, among students of the Faculty of Physical Education and Sports Sciences. In addition to that, it aimed at identifying the differences between the level of self-confidence and its relationship to self-confidence between the four stages of study. The results showed that there is a significant relationship between self-confidence and the body image of female college students